Doxycycline monotherapy for pyoderma vegetans: a case report - Jihane Belcadi; Sara Oulad Ali; Fatima-Zahra Sassine; Mariame Meziane; Karima Senouci (Taylor & Francis Group, 2024)
AbstractBackground: Pyoderma vegetans (PV) is a rare neutrophilic dermatosis of unknown etiology. Currently, there are no treatment guidelines for PV. Systemic steroids are often used as first-line therapy, but recurrence upon discontinuation or tapering is common.Materials and methods: We tested the efficacy of doxycycline at a dose of 200 mg/d to treat resistant PV.Results: After 4 weeks of treatment we noticed a significant improvement in the clinical appearance of PV.Conclusions: Our case demonstrates the potential utility of doxycycline as a systemic steroid-sparing agent in the treatment of PV.